EU and Russia in the Black Sea Region: Increasingly Competing Interests? - Niklas Nilsson (Romanian Journal of European Affairs)
This article examines two fields of geopolitical competition in the Black Sea region, in which an increasing EU involvement is increasingly challenging Russian interests. First, the EU’s effort to diversify its energy sources through new transportation routes is meeting competition in the form of Russian-sponsored projects. The EU has realized the partial incompatibility of Russian and EU interests in this regard; however, the lack of cohesion within the EU prevents the formation of common external energy policies. Second, the EU is increasingly recognizing its interest in engaging with conflict resolution in the region. This also runs contrary to Russian strategy, which strives to maintain the status quo in the conflicts rather than working for solutions, in order to maintain Russian leverage over the South Caucasus and Moldova. In this field, the EU has yet to officially recognize its interest conflict with Russia. However, due to the intertwinement of the conflict resolution processes with the EU’s deeper policy goals in the Black Sea region, namely the promotion of a stable, secure and democratic European neighborhood, the EU will likely find it increasingly difficult to pursue its key interests in the region, while simultaneously maintaining a passive stance towards Russian policies in the region.